Penyuluhan Kesehatan Tetang Memotivasi Untuk Vaksinasi Covid-19 Kepada Para Pedagang Pasar Pelas Kecamatan Kras Kabupaten Kediri Tahun 2021 - Ririn Imanita; Faiz Amiruddin (LP3M IAIFA Kediri, 2021)
Covid-19 is a virus caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a new type of disease that is prolonged and can cause respiratory problems, ranging from mild symptoms to severe symptoms such as flu, to lung infections, and pneumonia. Vaccination is one of the most effective ways and prevents infectious diseases with the aim of reducing morbidity and mortality. Seeing the current situation and conditions, Covid-19 is increasingly spreading and has a prolonged impact everywhere. The market is one of the riskiest places, especially market traders, so it is very important to be given counselling regarding the Covid-19 vaccination. The purpose of this service is to remind the public to continue to comply with health protocols at the welding market as recommended by the government and to motivate the Covid-19 vaccination to the public, traders and buyers. This research method uses the PAR (Participatory Action Research) method, which involves all parties to find solutions to problems and issues circulating in the community. The result of this service is that the resource persons are pleased or have been vaccinated against Covid-19. One of the factors that affect the covid-19 vaccination is age, education, occupation, and co-morbidities. And it is recommended that in motivating the Covid-19 vaccination to focus on the age of 40 years and over and add insight with media such as radio, television, and social media and don't forget to keep praying to Allah SWT.